Diagnosis dan Tatalaksana Epilepsi pada Subcortical Band Heterotopia: Sebuah Kasus Langka - Stella Natadidjaja; Gilbert Tangkudung; Herlyani Khosama (NEURONA, 2021)
Abstract Subcotical band heterotopia (SBH) is characterized by symmetrical and bilateral bands of heterotopic gray matter, located between the ventricular wall and the cortical mantle, and clearly separated from both. It is caused by genetic mutations. It’s a rare disorder with only a few hundred cases reported in literature till now and most of the patients were females. Clinical symptoms typically include recurrent seizures and intellectual delay. Treatment is mainly symptomatic and may include antiepileptics, although some cases may be refractory to medical therapy. Here we report a rare case of 13-year old girl with SBH in Indonesia with seizures that was responded to anti epileptic medication. Keywords:double cortex syndrome, epilepsy, subcortical band heterotopia